2013
DOI: 10.4067/s0718-19572013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bioactive molecules isolated from sea cucumber Athyonidium chilensis

Abstract: 4Agri-Food Laboratories-Concepción, SGS Chile Ltda. Américo Vespucio 820, Parque Industrial Las Arucas, Talcahuano, ChileResumen.-En la última década se ha incrementado el interés por la búsqueda de moléculas con potencial biomédico y amigable para el ambiente. Desde esta perspectiva, la búsqueda de principios bioactivos de origen marino ha permitido valorar la diversidad biológica presente en los ecosistemas acuáticos. En el Phylum Equinodermata, se destaca la familia Holothuridae, por su capacidad de sinteti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…The decomposition of the parent ion can also be triggered by the loss of sugar moiety, namely Glc, MeGlc, Xyl, and Qui followed by the aglycone which generated the product ions indicated in Figure 3i. It should be noted that the major characteristic peaks at 493, 507 and 511 correspond to either the sodiated partial glycoside compositions or the sodiated aglycone moieties [12,59,77,106], which further confirmed the presence of isomeric saponins. The full analysis can be seen in Supplementary Figure S2.…”
Section: Resultsmentioning
confidence: 73%
“…The decomposition of the parent ion can also be triggered by the loss of sugar moiety, namely Glc, MeGlc, Xyl, and Qui followed by the aglycone which generated the product ions indicated in Figure 3i. It should be noted that the major characteristic peaks at 493, 507 and 511 correspond to either the sodiated partial glycoside compositions or the sodiated aglycone moieties [12,59,77,106], which further confirmed the presence of isomeric saponins. The full analysis can be seen in Supplementary Figure S2.…”
Section: Resultsmentioning
confidence: 73%
“…Maybe, the lack of the antibiotic activity observed in this study was due to natural differences among species or because they produce apolar antibiotic substances not extracted with our methodology. The holothurian Athyonidium chilensis produce saponins that inhibit the growth of Staphylococcus aureus but were extracted with a different methodology using more apolar solvents like dichloromethane and methanol (Sottorff et al, 2013). Therefore, other extracted methodologies could be recommended to determine the presence of antibiotic substances in Chilean species of classes Holothuroidea, Asteroidea, Gastropoda and Ascidiacea.…”
Section: Discussionmentioning
confidence: 99%
“…In Valparaiso Bay at central Chile, the southern region and the Antarctica continent, many studies have identified bacteria, algae and benthic organisms as a new source of bioactive compounds with potential application as a news antibiotics, antivirals or antitumoral drugs (Henriquez et al, 1979;Hayashida-Soiza et al, 2008;Jiménez et al, 2011;Sottorff et al, 2013;Claverías et al, 2015;Arnau et al, 2016;Undabarrena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They have high commercial value coupled with increasing global production and trade (Bordbar et al, 2011). In a recent study, the smallest peptide fragment of a beta-thymosin detected in the coelomocytes of Mediterranean sea-urchin Paracentrotus lividus showed the common chemical-physical characteristics of AMPs (Schillaci et al, 2012).The characterization of a purified extract obtained from Athyonidium chilensis (Holothuria) by chromatographic and mass spectrometric techniques was identified as holothurinoside D. The biological activity of the purified extract showed antibacterial, antifungal and cytotoxic activity on a neuroblastoma cell line (Sottorff et al, 2013).…”
Section: Introductionmentioning
confidence: 97%